Deteriorasi Aspek Perlindungan Lingkungan Hidup Akibat Pembatasan Partisipasi Publik dalam Proses Amdal Pasca UU Cipta Kerja - Meliala, Dewi Ari Shia Wase; Elvetta, Shisca (Kertha Patrika; Vol 44 No 2 (2022)DO - 10.24843/KP.2022.v44.i02.p.06, 2022)
Every development activity must always adhere to the principles of sustainable development in the context of implementing environmental protection. Therefore, it is necessary to have a form of study on every business activity that has an important impact on the environment, through an Environmental Impact Assessment (EIA) mechanism as an instrument of preventive environmental administration. Seeing the important impact on the environment, of course it will be a concerns and responsibility of all parties (the public) to be involved in the EIA process until making decisions of environmental feasibility as an embodiment of the participatory principle. However, after the Job Creation Act, the involvement of public participation in the EIA process is considered to have been reduced. Based on this problem, this study aims to determine the concept of public participation in environmental permit and the implications of Job Creation Act on the role of public participation in the EIA process. This study uses a normative juridical method in the form of an analysis of the principles, rules, and provisions of laws and regulations, also accompanied by a relevant approach. The result of the study shows that there are 3 (three) forms of restrictions on public participation in the EIA process after the Job Creation Act. First, restrictions on the preparation stage that only involve directly affected communities. Second, restrictions on community elements in the Environmental Feasibility Test Team, and the third is restrictions due to the objection provision that have been removed. Finally, these three forms of restrictions by and by affect the reduction of environmental protection. Keywords: Environmental Impact Assessment, Public Participation, Job Creation Act Setiap aktivitas pembangunan harus senantiasa berpegang pada prinsip-prinsip pembangunan yang berkelanjutan dalam rangka pelaksanaan perlindungan lingkungan hidup. Karena itu, perlu adanya suatu bentuk kajian terhadap setiap usaha kegiatan yang memiliki dampak penting pada lingkungan hidup melalui sebuah mekanisme Amdal sebagai instrumen administrasi lingkungan yang bersifat preventif. Melihat adanya dampak penting pada lingkungan, tentunya akan menjadi kepentingan dan tanggung jawab semua pihak (publik) untuk dapat terlibat di dalam proses Amdal hingga pengambilan keputusan kelayakan lingkungan sebagai perwujudan dari asas partisipasif. Namun pasca UU Cipta Kerja, keterlibatan partisipasi publik dalam proses Amdal dinilai telah direduksi. Berdasakan permasalahan tersebut, penelitian ini bertujuan untuk mengetahui konsep partisipasi publik dalam perizinan lingkungan dan implikasi UU Cipta terhadap peranan partisipasi publik dalam proses Amdal. Penelitian ini menggunakan metode yuridis normatif berupa analisis terhadap asas, kaidah, dan ketentuan peraturan perundang-undangan, juga disertai dengan pendekatan yang relevan. Hasil penelitian menunjukkan bahwa terdapat 3 (tiga) bentuk pembatasan partisipasi publik dalam proses Amdal pasca UU Cipta Kerja. Pertama, pembatasan pada tahap penyusunan yang hanya melibatkan masyarakat terdampak langsung. Kedua, pembatasan unsur masyarakat di dalam Tim Uji Kelayakan Lingkungan. Ketiga, pembatasan akibat dihapusnya ketentuan upaya keberatan. Dimana ketiga bentuk pembatasan ini yang pada akhirnya berpengaruh terhadap tereduksinya aspek perlindungan lingkungan hidup. Kata Kunci:  Amdal, Partisipasi Publik, UU Cipta Kerja